Analysis of Demographic Changes and Changes in Public Consumption Patterns in the Tourism Industry in Denpasar City - Tubalawony, Jacsy; Setiadi, Bekti; Harsono, Iwan; Masrur , Muhamad (Westscience Press, 2024)
This research delves into the dynamic interplay between demographic changes and public consumption patterns within the tourism industry of Denpasar City. A sample of 260 participants, strategically stratified across key demographic variables, provides a nuanced understanding of the city's evolving population dynamics and the spending behaviors of residents and tourists. The findings reveal a mean annual population growth rate of 2.5%, a notable shift towards a younger demographic, and a rich cultural diversity within the city. Tourist expenditure, with a mean spending of USD 80 per visitor, illustrates key allocation trends across accommodation, dining, and activities. Regression analysis demonstrates significant correlations between demographic variables (age, income, cultural background, and educational attainment) and spending patterns. The results underscore the importance of adaptive strategies for stakeholders to cater to diverse preferences and foster sustainable tourism development in Denpasar City.